2005
DOI: 10.1016/s1808-8694(15)31196-4
|View full text |Cite
|
Sign up to set email alerts
|

Personalized vestibular rehabilitation: medical chart survey with patients seen at the ambulatory of otoneurology of I.S.C.M.S.P.

Abstract: It was possible to conclude that the PVR program is an effective resource in the treatment of otoneurologic symptoms of patients, consequently improving their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
2
8
0
1
Order By: Relevance
“…About the comorbidities found in this study (Table 3), were similar to those found in the works of Nishino et al [8], Horunbia [17] and Fetter [18] the indication of repositioning maneuvers and Vestibular Rehabilitation, even without the need for otoneurological additional tests [5].…”
Section: Discussionsupporting
confidence: 89%
“…About the comorbidities found in this study (Table 3), were similar to those found in the works of Nishino et al [8], Horunbia [17] and Fetter [18] the indication of repositioning maneuvers and Vestibular Rehabilitation, even without the need for otoneurological additional tests [5].…”
Section: Discussionsupporting
confidence: 89%
“…The distribution of the sample regarding gender and average age (Table 1) showed that dizziness was prevalent in female patients in this study, consistent with prior literature [5] [6]. Women seek medical care more frequently than men, regardless of factors such as the variation of the monthly hormonal cycle and menopause, which exhibits dizziness as a primary symptom [7] [8].…”
Section: Discussionsupporting
confidence: 87%
“…As complementary therapy or only therapy, vestibular rehabilitation (VR) is an excellent therapeutic choice for patients with vestibular disorders. Besides reducing vestibular symptoms, VR also has a prophylactic intent, it helps reestablish the patients' trust in themselves, reduces stress and improves social relations and life quality [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%